P.109 Diagnostic Yield of Targeted Exome Sequencing in West Syndrome. (November 2021) - Parfyonov, M; Guella, I; Evans, DM; Adam, S; DeGuzman, C; Van Allen, MI; Boelman, C; Nelson, TN; Farrer, MJ; Connolly, MB; Demos, M
Abstract : Background: West syndrome (WS) is characterized by the onset of epileptic spasms usually within the first year of life. Global developmental delay with/without regression is common. Advances in high-throughput sequencing have supported the genetic heterogeneity of this condition. To better understand the genetic causes of this disorder, we investigated the results of targeted exome sequencing in 29 patients with WS. Methods: Whole exome sequencing (WES) was performed on an Ion Proton TM and variant reporting was restricted to sequences of 620 known epilepsy genes. Diagnostic yield and treatment impact are described for 29 patients with WS. Results: A definitely/likely diagnosis was made in 10 patients (34%), which included 10 different genes ( ALG13, PAFAH1B1, SLC35A2, DYNC1H1, ADSL, DEPDC5, ARX, CDKL5, SCN8A, STXBP1 ) known to be associated with epilepsy or WS. Most variants were de novo dominant (X-linked/autosomal) except for ARX (X-linked recessive) and ADSL (autosomal recessive). 4 out of 10 (40%) had a genetic diagnosis with potential treatment implications. Conclusions: These results emphasize the genetic heterogeneity of WS. The high diagnostic yield, along with the significant genetic variability, and the potential for treatment impact, supports the early use of this testing in patients with unexplained WS.